2016
DOI: 10.1167/iovs.15-18738
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Head Measurements With Optical Coherence Tomography: A Phantom-Based Study Reveals Differences Among Clinical Devices

Abstract: PurposeOptical coherence tomography (OCT) can monitor for glaucoma by measuring dimensions of the optic nerve head (ONH) cup and disc. Multiple clinical studies have shown that different OCT devices yield different estimates of retinal dimensions. We developed phantoms mimicking ONH morphology as a new way to compare ONH measurements from different clinical OCT devices.MethodsThree phantoms were fabricated to model the ONH: One normal and two with glaucomatous anatomies. Phantoms were scanned with Stratus, RTV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…Previous studies have highlighted that these differences are likely to be due to both the instruments internal algorithms as well as scan patterns. [ 29 , 30 ] Spectralis derived optic disc measurements consistently produced the weakest correlations and the greatest number of outliers with beta PPA being a main contributing factor. Analysis of these outliers showed that variations in disc area measurements between the two instruments resulted from markedly different delineation of the BMO location in the areas of beta PPA ( Fig 3B ).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have highlighted that these differences are likely to be due to both the instruments internal algorithms as well as scan patterns. [ 29 , 30 ] Spectralis derived optic disc measurements consistently produced the weakest correlations and the greatest number of outliers with beta PPA being a main contributing factor. Analysis of these outliers showed that variations in disc area measurements between the two instruments resulted from markedly different delineation of the BMO location in the areas of beta PPA ( Fig 3B ).…”
Section: Discussionmentioning
confidence: 96%
“…However, literature has shown that OCT data from the leading OCT brands are comparable. [25][26][27] Several studies have looked at the optic disc size of people across races. One of the key differences highlighted is the larger optic disc size in people of African descent.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the mean RNFL thickness between Stratus and Spectralis OCT (106.2 ± 6.9 µm vs 100.0 ± 7.3 µm) have been reported, and concluded not to be interchangeable in a clinical evaluation [6]. Agrawal et al showed that built-in algorithms may be the main cause for differences in the measured layer thicknesses [9]. A reported mean difference between Spectralis and Cirrus devices RNFL thicknesses was 6.7 µm, when device's own software was used, and the thickness difference was reduced to 0.1 µm when custom software was used [5].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, current commercial OCT devices have a poor inter-brand repeatability regarding the assessment of the retinal layers, limiting the interchangeable use of different devices. Differences between devices have been observed both in human eyes [1][2][3][4][5][6][7] and in specially developed phantom eyes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation